Is Social Distancing Law the New Normal? Forced Shift to Media Online Learning and Its Effectiveness: A Moderating Role of Student Engagement During the Pandemic of COVID-19 - Liu, Qing; Mo, Shuwen (Frontiers in Psychology, 2022)
The author aims to investigate the role of social distancing law the new normal, Force-Shift to media online learning and its effectiveness- A moderating role of student engagement during the pandemic in this study. The current research is based on Social learning theory (SLT) that is trying to imitate other people's behavior, perceptions, and emotional responses. The Data has been collected from the different universities of china. We were able to collect data using the stratified sampling method and collecting data through online media via google form. The direct, mediating, and moderating effects of the variables were evaluated using partial least square structural equation modelling in this study (PLS-SEM), using the Smart PLS software 3.0. According to the findings, Forced-shift to media online learning acts as a mediator between the lack of social interaction, perceived harm, perception of maintaining social distancing and law, and the effectiveness of media online learning. In addition, student engagement appears to be a moderator between the force-shift to media online learning and its effectiveness. Future research could focus on learning more about the various activities that can encourage engagement in an online setting. Teachers must go outside the boundaries to come up with themes that allow students to connect while studying. Instructors and educational institutions will benefit from the study since it will enable them codify ways for enhancing social interaction in online learning and examine to increase their effectiveness of media online learning.